Epidemiological characteristics of invasive Aspergillus isolates: Morphology, drug susceptibility, and mutations in azole drug targets - Wei Zhang; Hongxia Zhang; Minghua Zhan; Ran Jing; Xinsheng Wang; Zhihua Zhang (Journal of Infection and Public Health)
Background: The global epidemiology of aspergillosis varies and is influenced by various factors. To elucidate the disease burden and identify effective control strategies, the epidemiological characteristics of Aspergillus infections have to be investigated. The aim of this study was to assess the epidemiological characteristics of various Aspergillus species, including their morphological features, species identification, and in vitro susceptibility to nine antifungal agents in a large tertiary hospital in northern China. Methods: Ninety-five clinical isolates of Aspergillus were collected from patients. Aspergillus species identification was performed using conventional morphological methods, MALDI-TOF MS, and gene sequencing. In vitro susceptibility to nine antifungal agents was evaluated using the Sensititre YeastOne system. Target genes (cyp51A and cyp51b) of A. tubinazole were sequenced using the Sanger method. Results: Aspergillus fumigatus, Aspergillus niger, Aspergillus flavus, Aspergillus tubingensis, and Aspergillus terreus were the most common isolated species. Rare species included Aspergillus tamarii, Aspergillus usamil, Aspergillus versicolor, Aspergillus udagawae, Aspergillus lentulus, Aspergillus sydowii, and Aspergillus quadrilineatus. Pulmonary infections accounted for 86.3 % (82/95) of collected cases, and the in-hospital mortality rate was 22.1 %. The median minimum inhibitory concentration (MIC) range of amphotericin B was 1.5–4 mg/L. The MIC range of triazoles against Aspergillus species, excluding Aspergillus udagawae and Aspergillus lentulus, was 0.12–0.5 mg/L. The median minimum effective concentration range of echinocandins was < 0.008–0.03 mg/L. Non-wild-type resistance to amphotericin B was observed in 29.6 % (16/54) of Aspergillus fumigatus isolates, and non-wild-type resistance to voriconazole was observed in 11.1 % (1/9) of Aspergillus tubingensis isolates. Moreover, CYP51A and CYP51b of Aspergillus tabinensis had 2–29 and 10–13 nucleotide mutations, respectively. Conclusion: Patients with non- Aspergillus fumigatus infection accounted for 43.2 %. The T256A amino acid substitution in CYP51A of Aspergillus tabinensis did not lead to increased azole drug MICs.